Analysis of Nonlinear Dynamic Characteristic of Elliptic Gear with Friction - Fang Wen; Haizhao Dang; Ganwei Cai; Xingbo Liang (Jixie chuandong)
The bending torsion coupling model of elliptical gear pair is established， including the factors of tooth surface friction， time-varying stiffness， damping， backlash and so on. Different parameters are selected and solved by 4~5-step Runge-Kutta numerical method to analyze the nonlinear dynamic characteristics of elliptic gear pair. It can be seen from the analysis that， under certain conditions， when the speed is low， the elliptical gear system is in the stable and regular single period motion stage. The quasi periodic motion， appear with the unstable chaotic motion alternatively under the circumstance of the increasing of the rotational speed. The system motion can be more stable under the circumstance of increasing of friction coefficient and damping ratio， while the system motion can be more unstable under the circumstance of increasing of stiffness coefficient and eccentricity ratio.